Correlation Analysis Between Volatile Flavor Compounds and Microbial Communities During the Fermentation from Different Ages Mud Pits of Wuliangye Baijiu - Yanping Lu; Yalan Li; Bing Wan; Yuzhu Li; Jian Su; Jia Zheng; Dong Zhao; Yan Xu (Fermentation)
The continuous usage years of mud pits significantly impact the formation of volatile flavor compounds (VFCs) in Wuliangye Baijiu fermentation, yet their role in regulating initial microbial diversity and VFCs during fermentation remains unclear. This research analyzed the dynamic relationships among microorganisms, physicochemical characteristics, and VFCs from two different aged mud pits (continuous usage for 20 years: JC20 and 40 years: JC40). As fermentation advanced, VFCs increased, with JC40 showing a greater increment than JC20. Furthermore, the predominated microorganisms during fermentation of two pits were significantly different, resulting in distinct microbial successions. And the microbial diversity in JC40 was higher than JC20 at the fermentation anaphase from different layers of zaopei samples. Microbes were identified that highly correlated with physicochemical properties and VFCs, and the important microbial species differed between the two pits, proving the importance of mud pit continuous usage years for Wuliangye Baijiu production.